Patterns of Tarnished Plant Bug (Hemiptera: Miridae) Resistance to Pyrethroid Insecticides in the Lower Mississippi Delta for 2008–2015: Linkage to Pyrethroid Use and Cotton Insect Management. Issue 2 (15th March 2018) - Parys, Katherine A; Luttrell, Randall G; Snodgrass, Gordon L; Portilla, Maribel R
Abstract: Populations of tarnished plant bug, Lygus lineolaris (Palisot de Beauvois) (Hemiptera: Miridae), from the Lower Mississippi Delta regions of Arkansas, Louisiana, and Mississippi were evaluated from 2008 through 2015 for susceptibility to pyrethroid insecticides using a diagnostic-dose assay with permethrin. Resulting data add to the compilation of pyrethroid susceptibility data carefully tracked in this pest since 1994 and provide continuing evidence of high frequencies of pyrethroid resistance in field populations of the tarnished plant bug. Resistance levels are variable, and some populations remain susceptible suggesting practical value in the continued use of the diagnostic-dose assays prior to pyrethroid treatments. Recent studies with dose–response models suggest that levels of pyrethroid resistance in some populations may still be evolving, with some populations requiring higher doses to reach levels of control comparable to those observed 10 yr ago. Concerns for frequent use of multiple classes of insecticides and possible selection for tarnished plant bugs with metabolic resistance mechanisms capable of detoxifying available insecticide chemistries warrant continued efforts to manage resistance in this important crop pest. Associations among measured pyrethroid resistance levels, published data on annual use of pyrethroid insecticides, and annual estimates of cotton insect losses and control costs were explored and summarized for the 8 yr of this investigation. Mortality of tarnished plant bugs at the diagnostic-dose of permethrin was negatively correlated with kilograms of pyrethroids applied per acre of harvested cropland.